Placental histology related to fetal brain sonography - Rosier-van Dunné, F M F; van Wezel-Meijler, G; Kaschula, R O C; Wranz, P A B; Odendaal, H J; de Vries, J I P (Archives of disease in childhood. Fetal and neonatal edition, 2011)
Background Chronic hypoxia and inflammatory processes can induce placental disturbances that may indirectly lead to perinatal brain injury. Objective To study histological features of the placenta in relation to echogenicity changes in the periventricular white matter, ventricular system and basal ganglia/thalami of the fetal brain. Design Prospective study of 77 fetuses between 26 and 34 weeks gestational age with their placentas. The pregnancies were complicated by hypertensive disorders (n=42) or preterm labour (n=35). Results Of the placentas 79% showed uteroplacental hypoperfusion, inflammation or a combination. Transvaginal ultrasound examination of the brain revealed echogenicity changes in 73% of the fetuses (44 mild, 29 moderate). Moderate brain echogenicity changes (periventricular echodensity (PVE) grade IB: increased echogenicity brighter than choroid plexus, intraventricular echodensity (IVE) grade II and III: echodensity filling ventricle respectively <50% and ≥50%; basal ganglia/thalamic echodensity (BGTE): locally increased echogenicity within basal ganglia/thalami) were equally distributed over cases with uteroplacental hypoperfusion and inflammatory features in the placenta. PVE grade IB was always associated with placental pathology. The sensitivity and negative predictive value of placental pathology for moderate echogenicity changes were high (0.91 and 0.88, respectively), while the specificity and positive predictive value were low (0.27 and 0.34, respectively). Conclusions Normal placental histology predicted no or mild echogenicity changes, supporting the view that the latter are physiological. Placental pathology was always present in cases with grade IB PVE, presumed to represent mild or early forms of white matter injury. Both uteroplacental hypoperfusion and inflammatory features were seen in placentas from pregnancies with hypertensive disorders.